GLASS CEILING FACTORS AFFECTING WOMEN CAREER PROGRESSION - G, Christena Sneha; Jayanthi, V.; Jayanthi, V. (International Journal of Psychosocial Rehabilitation, 2020)
It is well known that in the concept of glass ceiling effect, the gender disadvantages are considered to be high at the top level of the careers than at the lower levels. This become a bigger disadvantage in the women’s career. A rigorous investigation needs to be done in such issues. The entire study was descriptive, and the study attempts to identify factors which contributes to the glass ceiling effects of women career progression. The data is collected from 57 women respondents employed in IT sectors.